ARTIFICIAL INTELLIGENCE IN EDUCATION: BENEFITS, CHALLENGES, AND IMPLICATIONS FOR MODERN TEACHING PRACTICES - Djurayeva Surayyo Vosiq qizi; Qurbonova Kamola O’ktam qizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract:Artificial Intelligence (AI) has emerged as one of the most influential technologies shaping contemporary education. The integration of AI-powered tools into teaching and learning environments has transformed educational practices by enhancing personalized learning, improving assessment processes, and increasing accessibility to educational resources. At the same time, the rapid expansion of AI technologies has raised significant concerns regarding academic integrity, data privacy, ethical considerations, and the potential reduction of human interaction in educational settings. This theoretical review examines the major advantages and disadvantages of AI in education through a comprehensive analysis of recent scholarly literature. The study explores how AI contributes to teaching effectiveness, student engagement, and learning outcomes while also addressing challenges associated with technological dependency and algorithmic bias. The findings indicate that AI has substantial potential to support educational innovation; however, its implementation should be guided by ethical principles and pedagogical objectives. The paper concludes that a balanced integration of AI and human-centered teaching approaches is essential for maximizing educational benefits and minimizing associated risks.